2007
DOI: 10.1097/01.inf.0000261126.60283.cf
|View full text |Cite
|
Sign up to set email alerts
|

Coagulant and Fibrinolytic Status in Tuberculous Meningitis

Abstract: The hypercoagulable state in childhood TBM is comparable to that described in adults with pulmonary tuberculosis and may further increase the risk for infarction. Therapeutic measures that reduce the risk for thrombosis could therefore be potentially beneficial in childhood TBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…In support of these previous findings, our patients with TBM had lower MPV and higher platelet counts compared with those of controls and BM patients. With respect to a possible mechanism explaining our findings, both BM and TBM are associated with an intense inflammatory state (increased oxidative stress, pro-inflammatory cytokine production, and inflammatory cell activation) as well as with a prothrombotic state (endothelial dysfunction, vasculitis, and pro-coagulant mediators) [23][24][25][26]. Longer disease duration in TBM could result in an altered megakaryopoiesis due to chronic exposure to an inflammatory environment.…”
Section: Discussionmentioning
confidence: 88%
“…In support of these previous findings, our patients with TBM had lower MPV and higher platelet counts compared with those of controls and BM patients. With respect to a possible mechanism explaining our findings, both BM and TBM are associated with an intense inflammatory state (increased oxidative stress, pro-inflammatory cytokine production, and inflammatory cell activation) as well as with a prothrombotic state (endothelial dysfunction, vasculitis, and pro-coagulant mediators) [23][24][25][26]. Longer disease duration in TBM could result in an altered megakaryopoiesis due to chronic exposure to an inflammatory environment.…”
Section: Discussionmentioning
confidence: 88%
“…The use of aspirin has been researched in TBM, since it is antithrombotic and possibly neuroprotective. Children with TBM and adults with pulmonary TB have been shown to have hypercoagulation, which may contribute to the development of ischemia [102]. However, a study performed in children with TBM showed no significant effect on either mortality or neurological deficits with either low-or high-dose aspirin regimens [103].…”
Section: Strokementioning
confidence: 90%
“…A hypercoagulable state in TBM has been reported and may increase the risk of infarction [47]. There is a decrease of anticoagulant (Protein S) and an increase of procoagulant factor (Factor VIII).…”
Section: Coagulation and Fibrinolytic Status In Tuberculous Meningitismentioning
confidence: 99%
“…This hypercoagulable state is more pronounced in stage III than in stage II TBM. These changes in procoagulant, antithrombotic, fibrinolytic, platelet and vascular endothelial functions could contribute to increased risk of thrombosis and infarction [47].…”
Section: Coagulation and Fibrinolytic Status In Tuberculous Meningitismentioning
confidence: 99%